Prodotti della tradizione e contenuto di amine biogene alternative alla Low tyramine diet per la sostenibilità dei prodotti di nicchia e la salubrità del consumatore - Giovanna Suzzi; Rosanna Tofalo; Maria Schirone (Italian Journal of Agronomy, 2011)
Biogenic amines (BA) are present in a wide range of foods and mainly can be produced in high amounts by microorganisms through the activity of amino acid decarboxylases. Excessive consumption of foods with large concentrations of these compounds can induce adverse reactions such as nausea, headaches, rashes and changes in blood pressure. These problems are more severe in consumers with less efficient detoxification systems because of their genetic constitution or their medical treatments. The most common and powerful BA found in foods are histamine, tyramine and putrescine. Actually, there is no specific legislation regarding BA content in many fermented products, except for histamine; it is the only BA for which maximum levels in fish products have been set. So, it is generally assumed that these compounds should not be allowed to accumulate. Many factors such as bacterial density, synergistic effects between microorganisms, level of proteolysis (availability of substrate), pH, salt, use of starter cultures, sanitization procedures adopted and conditions and time of ripening process are found to have limiting effects on the build-up of amines. Moreover, improved knowledge of the factors involved in the synthesis and accumulation of BA should lead to reduce in their incidence in foods.